THE ROLE OF ROOM ATTENDANTS ON CUSTOMER SATISFACTION AT THE IBIS ACARDIA HOTEL JAKARTA - Prawiraharja, Ananto; Fakihuddin, Muhammad (Akademi Komunitas MAPINDO, 2022)
The purpose of writing this research is to determine the role of the room attendant on customer satisfaction at the Ibis Arcadia Jakarta hotel. Hotel is one type of accommodation that used by many tourists as a place to stay, eat, drink and various services and other facilities with payment. Hotel business continues to grow rapidly in Indonesia. Guest service is one of the most influential things for the guest experience. The department at the hotel whose role to provide guest services so that they feel satisfied and want to visit again is the room attendant. In carrying out his duties, the room attendant is directly related to all hotel guests and as a good room attendant, he must be able to give positive first impressions. The type of research method used in this journal is qualitative. Researchers look for information or data sources from reviews about how room attendants provide good service to every guest who comes to the Ibis Arcadia Hotel Jakarta. Based on observations by researchers, researchers found that the room attendant had performed their duties and responsibilities quite well in accordance with the standards set by the hotel. However, it would be better to improve the cleanliness of the room attendant, because the room attendant has an important role in cleaning and maintaining guest rooms Keywords: Customer Satisfaction, Hotel, Room Attendant